Diversi Restoratif Anak Yang Berhadapan dengan Hukum di Yogyakarta: Sebuah Analisa Demokrasi, Kepercayaan, Kewarganegaraan - Ameylia Puspita Rosa Dyah Ayu Arintyas; Hakimul Ikhwan; Muhadjir Darwin (Prodi Ilmu Pemerintahan FISIP Universitas Komputer Indonesia, 2023)
Children are a vulnerable group with the potential to face the law. Children who conflict with the law then experience multiple levels of vulnerability due to their inability to develop themselves without restrictions and stigmatization from society. Globally, children in conflict with the law have been instructed to get the opportunity for restorative justice, namely justice intended to protect the interests of children. Indonesia has also established restorative justice through a diversion policy scheme. However, to date, this diversion policy has yet to be fully implemented due to a lack of legitimacy from the community and a lack of operational resources. Therefore, researchers feel that research on this issue is essential because of its significant impact on legal reform objectives in Indonesia. This research used the perspective of democracy, trust, and citizenship to accommodate participatory values and obligations in restorative practices. Qualitative methods using critical informant interview data were used in this research. The results are that restorative justice and restorative policies can accommodate democratic practices. However, for their implementation to be more optimal, there needs to be an increase in trust and civic awareness.